1631c Recent changes to the acgih hand activity level tlv. (24th April 2018) - Rempel, D
Abstract : The ACGIH Hand Activity Level (HAL) Threshold Limit Value (TLV) is a risk assessment tool designed to protect workers, who perform repetitive hand exertions for 4 or more hours per day, from distal upper extremity disorders. Recent large, longitudinal studies, provide strong evidence that repetitive forceful hand exertions increase risk for occupational wrist tendinosis and carpal tunnel syndrome. 1, 2, 3 In the Harris-Adamson study, 3 forceful hand exertions (e.g., >9N pinch or >45N power grip force) and the%time performing forceful hand work increased risk. Based on these and psychophysics studies, 4 hand exertions should be considered in risk assessment models if they are above 10% of posture specific strength. In addition, in these large studies, the prior HAL TLV action limit (0.56) was not sufficiently protective 5 and, therefore, has been revised. The name of this TLV was changed to Hand Activity (HA) TLV. Other changes to the TLV will also be presented. References: . Harris C, Eisen E, Goldberg R, et al. Workplace and individual factors in wrist tendinosis among blue-collar workers: The San Francisco study. Scand J Work Environ Health2011;37(2):86–98. . Bonfiglioli R, Mattioli S, Armstrong T, et al. Validation of the ACGIH TLV for hand activity in the OCTOPUS cohort: A two-year longitudinal study of carpal tunnel syndrome. Scand J Work Environ Health2013;39:155–63. . Harris-Adamson C, Eisen EA, Kapellusch J, et al. Biomechanical risk factors for carpal tunnel syndrome: A pooled study of 2474 workers. Occup & Environ Medicine 2015;72:33–41. . Potvin JR. Predicting maximum acceptable efforts for repetitive tasks an equation based on duty cycle. Human Factors2012;54(2):175–188. . Kapellusch JM, Gerr F, Malloy EJ, et al. Exposure-response relationships for the ACGIH TLV for hand activity level: Results from a pooled data study of carpal tunnel syndrome. Scand J Work Environ Health2014;40:610–20.